1998
DOI: 10.1088/0953-2048/11/7/006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties of YBCO-Ag composite superconductors made by mixing with metallic Ag powder and solution

Abstract: The role of Ag additions in the microstructural evolution and related mechanical properties of YBCO has been studied. Various amounts of Ag have been added to YBCO by two different mixing techniques, i.e. in the form of metallic Ag powder and solution. The strength and fracture toughness of YBCO specimen increased with increasing Ag content, probably because of strengthening mechanisms resulting from Ag addition. In addition, YBCO-Ag composites showed higher values of strength and fracture toughness when Ag w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Figure 7 shows the inverse of the logarithmic derivative of the conductivity, χ −1 σ , as a function of temperature for GD sample (J = 800 mA/cm 2 ). The maximum of dρ/dT is signaled and can be observed a set of fluctuation regimes labeled by λ (1) cr , λ (2) cr , λ 1 (all observed above T P ) and s (observed between T CO and T P ). The exponent λ 1 = 0.55 ± 0.03 corresponds to homogeneous 3D fluctuations while the exponent λ (2) cr = 0.32 ± 0.03 characterizes the asymptotic regime precursor to the pairing transition, and consistent with the 3D − XY model [22].…”
Section: Fluctuation Regimesmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 7 shows the inverse of the logarithmic derivative of the conductivity, χ −1 σ , as a function of temperature for GD sample (J = 800 mA/cm 2 ). The maximum of dρ/dT is signaled and can be observed a set of fluctuation regimes labeled by λ (1) cr , λ (2) cr , λ 1 (all observed above T P ) and s (observed between T CO and T P ). The exponent λ 1 = 0.55 ± 0.03 corresponds to homogeneous 3D fluctuations while the exponent λ (2) cr = 0.32 ± 0.03 characterizes the asymptotic regime precursor to the pairing transition, and consistent with the 3D − XY model [22].…”
Section: Fluctuation Regimesmentioning
confidence: 97%
“…In Figure 5 we show the resistive transition of GB sample. The measurement was performed with a current density of 800 mA/cm 2 T results is plotted. The zero resistance temperature, T C0 , is achieved at approximately 91 K, and we can observe that T P ∼ = 93 K. Also, we can identify the temperature interval relevant for studying fluctuations in the normal phase (above T P ) and the regime dominated by mesoscopic granularity (close to the ρ = 0 state) [19].…”
Section: Fluctuation Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture toughness of YBa 2 Cu 3 O 7-x melttextured samples has been determined by Vickers indentation (Leblond-Harnois et al, 2000; Li et al, 1997;Yoshino et al, 2001;Cook et al, 1987;Fujimoto et al, 1992), and also by the single-edge notch beam (Joo et al, 1998) and bending (Giese et al, 1990) techniques. Values in the range of K IC =0.4-2.8 MPa·m 1/2 have been found, with a scattering attributed to differences between the techniques employed to obtain this parameter.…”
Section: B Fracture Toughnessmentioning
confidence: 99%
“…In addition, K IC is influenced by exact matrix composition. For instance, Joo et al (Joo et al, 1998), reported that the fracture toughness of YBa 2 Cu 3 O 7-x increased from K IC =1.60 MPa·m 1/2 to 2.80 MPa·m 1/2 by adding a 15% in volume of silver to the matrix.…”
Section: B Fracture Toughnessmentioning
confidence: 99%